EVALUASI KEBIJAKAN PADA INOVASI PELAYANAN ”SIPENTOLMANIS” DI KECAMATAN JETIS KABUPATEN MOJOKERTO - Fitri Rohmalia; Ertien Rining Nawangsari (Journal Publicuho, 2025)
SIPENTOLMANIS was created to facilitate administrative services. However, in its implementation, there are still obstacles such as the majority of rural communities with low literacy rates, and a lack of socialisation within the community. This study aims to describe the evaluation of policies in the implementation of SIPENTOLMANIS in Jetis District, Mojokerto Regency. The research method used is qualitative descriptive research with reference to evaluation theory, namely effectiveness, efficiency, adequacy, equalisation, responsiveness, and accuracy. Data collection techniques are carried out through interviews, observations, and documentation. The results of the SIPENTOLMANIS policy research have been evaluated by the evaluation criteria and have been proven to facilitate services for the community in the early post-pandemic period. However, the effectiveness and equalisation criteria are not optimal. There has been a decrease in users in 2024-2025, because people who are close to the District office prefer to come directly. It is recommended to increase service innovation that is closer to the community and website development to increase the number of SIPENTOLMANIS users.